Pengaruh Inovasi Adopsi Teknologi, Peran Pemerintah, Peran Lembaga Lokal, dan Modal Usaha Terhadap Kegiatan Ekonomi Nelayan di Desa Labuan Ijuk Kabupaten Sumbawa Besar - Wa Ode Hikmawati; Edi Irawan (Indonesia Economic Journal, 2026)
This study analyzes the effects of technological innovation adoption, the role of government, the role of local institutions, and business capital on the economic activities of fishermen in Labuan Ijuk Village, Sumbawa Besar Regency. The research is motivated by the persistently low welfare level of small-scale fishermen, which is influenced by technological limitations, constrained access to capital, the effectiveness of government policies, and the capacity of local institutions. The objective of this study is to examine the partial and simultaneous effects of each variable on fishermen’s economic activities. A quantitative approach was employed using a survey method, with capture fishermen as the unit of analysis. Primary data were collected through structured questionnaires and analyzed using multiple linear regression, supported by classical assumption tests and hypothesis testing. The results indicate that technological innovation adoption, government role, local institutional role, and business capital have positive and significant effects on fishermen’s economic activities, both partially and simultaneously. Business capital and technology adoption make dominant contributions to improving productivity and income stability, while the roles of government and local institutions function as supporting factors through facilitation, capacity building, and the strengthening of social networks. This study provides an empirical contribution to the development of coastal economic development studies by presenting an integrated analytical model at the village level. Practically, the findings serve as a policy reference for strengthening technology, access to capital, and institutional capacity to enhance fishermen’s welfare.